Three-dimensional High-Definition color Doppler flow imaging and vascular tumor biopsy to assess complex ovarian masses – a preliminary experience - Czekierdowski, Artur; Stachowicz, Norbert; Daniłoś, Jarosław; Kotarski, Jan (Menopause Review/Przegląd Menopauzalny, 2009)
Background: Recently, transvaginal three-dimensional High-Definition flow imaging (3D-HDF) has become available for studying morphology of blood vessels. Objectives: To assess if vascular morphology depicted by 3D-HDF differs between malignant and benign ovarian tumors and to evaluate if this method is superior to color pulsed Doppler sonography (CPD) or 3D power Doppler sonoangiography (3D-PD) in imaging of complex ovarian tumors vascularity. Material and methods: Ultrasound data of 38 women operated because of complex (unilocular-solid, multilocular, multilocular-solid and solid) ovarian masses were analyzed (Voluson E8, GE, Austria). Doppler measurements included peak systolic velocity (PSV), pulsatility index (PI) and resistive index (RI). 3D-PD tumor “biopsy” of the most vascularized part was used for the vascular index (VI), flow index (FI) and vascular-flow index (VFI) calculations. 3D-HDF was next activated and allowed to detect chaotic vs. normal blood vessel arrangement later analyzed with 4D View software (Kretz, Austria). Results: Mean age of women with benign (n=19) and malignant (n = 19) tumors was 39 yrs (range, 16-67) and 58 yrs (range 23-83), respectively. Mean PSV, PI and RI did not differ between both groups. Significant differences were found for all 3D-PD indices: VI (p = 0.02), FI (p = 0.02), VFI (p = 0.01). 3D-HDF was superior to both CPD and 3D-PD with respect to blood flow and small vessel imaging. Highly significant difference (c2 test, p = 0.0003) in the frequency of chaotic vessel arrangement was found between benign (10.5%) and malignant tumors (73.6%). Conclusions: Our preliminary data indicate that even small tumor vessels can be easily visualized when a systematic 3D-HDF analysis is performed on 3D data set volumes. The method provides better resolution for depicting malignant ovarian tumor vessels compared with CPD and 3D-PD sonoangiography.